2012
DOI: 10.1001/archpediatrics.2011.794
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult Preventive Health Care Guidelines

Abstract: Objectives: To (1) identify adolescent and adult clinical preventive services guidelines relevant to the young adult age group; (2) review, compare, and synthesize these guidelines, with emphasis on the extent to which professional guidelines are consistent with evidence-based guidelines developed by the US Preventive Services Task Force; and (3) recommend the next steps in the establishment and integration of preventive care guidelines for young adults. Design: Nonexperimental: an Internet search was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(54 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…76 Their guidelines can be applied to all age groups but pertain to the general population. 77 The American Society for Blood and Marrow Transplantation and others have jointly recommended system/organ-based screening and preventive practices for BMT long-term survivors.…”
Section: Infertility Resourcesmentioning
confidence: 99%
“…76 Their guidelines can be applied to all age groups but pertain to the general population. 77 The American Society for Blood and Marrow Transplantation and others have jointly recommended system/organ-based screening and preventive practices for BMT long-term survivors.…”
Section: Infertility Resourcesmentioning
confidence: 99%
“…Quantitative and qualitative research should be conducted to better delineate the specific types of care these youth receive (and lack), the continuity and quality of provider relationships they experience, and the degree to which they receive evidence-based care for chronic medical conditions during adolescence and the transition to adulthood. Current and former foster youth may benefit from a level of preventive health care beyond that which is recommended for general population youth, 32,33 including strategies to promote access to state-of-the-art interventions targeting modifiable cardiovascular risk factors such as diet, exercise, and smoking cessation. Training and resources for caseworkers, foster parents, and group home staff emphasizing the importance of continuity and quality of health care provider relationships in addition to timely access may also be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent review of preventive guidelines found that no specific guidelines exist for young adults, even though their developmental needs are markedly different from those of adolescents or older adults [21]. Primary care services should be reimbursed for preventive visits and should have care PRACTICE AND PUBLIC HEALTH POLICIES goals for young adults that include routine preventive screenings [21].…”
Section: Policy Recommendations To Improve Young Adult Healthmentioning
confidence: 99%
“…This critical issue has been addressed in recent legislative efforts to improve access to and quality of health care for all Americans. Many key provisions of the Patient Protection and Affordable Care Act (ACA) expand health insurance coverage options for young adults (ages [18][19][20][21][22][23][24][25] [2]. The ACA is a strong initial attempt to provide increased insurance coverage for young adults; however, the current provisions of the ACA are inadequate to address some of the systemic issues related to health care access and utilization among young adults.…”
Section: Introductionmentioning
confidence: 99%